PERANCANGAN PUSAT BUDAYA LAMPUNG PEPADUN DENGAN PENDEKATAN ARSITEKTUR NEO VERNAKULAR DI KOTA BANDAR LAMPUNG - Dimas Aditya Nugraha; Sri Kurniasih; Putri Suryandari (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2021)
The Lampung Pepadun Cultural Center in Bandar Lampung City is designed to provide cultural facilities and preserve the Lampung pepadun culture, providing facilities such as culinary and traditional house prototypes. With the application of Neo Vernacular Architecture. Architecture that aims to preserve local elements that have been formed and develop them into a modern style. This makes the appearance of the building more modern and has character in accordance with the function of the building as a building for the Lampung Pepadun Cultural Center. The people of Lampung really respect the customs that they adhere to. Adat is very important because it greatly influences the behavior, habits, and beliefs of the people of Lampung Pepadun. The people of Lampung Pepadun adhere to a patrilineal kinship system that adheres to the father's lineage in one family. Bandar Lampung City is a city located in Lampung Province, Indonesia. The city is bordered by South Lampung Regency and Pesawaran Regency.